Pengembangan Repository berbasis Archives Initiative Protocol for Metadata Harvesting (OAI-PMH) pada Standar Metadata Encoding and Transmission Standard (METS) dan MPEG-21 Digital Item Declaration Language (DIDL) - Taufiq Iqbal; Syarifuddin Syarifuddin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The purpose of this research is to build a repository model and feature the Archives Initiative Protocol for Metadata Harvesting (OAI-PMH) and the Metadata Encoding and Transmission Standard (METS) and MPEG-21 Digital Item Declaration Language (DIDL). The research model used is qualitative research and methods. Application development used is Fourth Generation Techniques (4GT). From the results of the development of the repository by involving the Archives Initiative Protocol for Metadata Harvesting (OAI-PMH) module on the Metadata Encoding and Transmission Standard (METS) and MPEG-21 Digital Item Declaration Language (DIDL), it has been applied to the repository application that was built. The test results using the OAI-PMH URL using the OVAL validator tool found that there were no problems and problems in validating and verifying data in the Identify, ListMetadataFormats, ListSets, ListIdentifiers, ListRecords, and XML Validation commands. While the test results show the success rate in crawling each metadata in the web repository, the average success rate of crawling metadata by Google Scholar is 90%, while the error is known to be 10% because some documents do not have complete metadata such as bibliography and uploaded documents.